The size of the substitution bias of inflation measurement in relation to the level of innovativeness of the European Union’s economies - Roszko-Wójtowicz, Elżbieta; Białek, Jacek (Wielkość obciążenia substytucyjnego pomiaru inflacji w relacji do poziomu innowacyjności gospodarek Unii Europejskiej, 2018)
The consumer price index (CPI) is a common measure of inflation. Similarly to the harmonised index of consumer prices (HICP), it is determined using the Laspeyres index, thus data on the consumption of the basket of goods do not have to be current. The Laspeyres index, using weights only from the base period, may not reflect changes in consumer preferences that occurred in the studied year. This is the reason for the formation of the so-called substitution bias in the measurement of inflation. The aim of the article is to assess the impact of the level of innovativeness of a given country’s economy on the occurrence of the substitution effect. The empirical part of the article is based on basic innovation indices, i.e. the SII, IOI, and GII. The assessment of the relationship between the level of innovativeness and the scale of the substitution effect was carried out based on the methods of multidimensional statistical analysis (including cluster analysis, the PROFIT method).
Econometrics = Ekonometria, 2018, Vol. 22, No. 4, s. 79-97
Keywords: cluster analysis; inflation measurement; substitution bias; innovativeness; innovation indices; PROFIT method